(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The Republic of Iraq occupies a distinguished geographical location that has great influences on the region in particular and on the Middle East region in general, on all economic, social and political levels. This is what requires Iraq to implement and develop the infrastructure for transport projects of all kinds, and link the ports of the northern Arabian Gulf to Europe through Iraq, Syria and Turkey. And Lebanon, making Iraq an important transit country for goods at the international level, adapting the procedures followed, decisions and customs regulations for transit transportation issued under the amended Customs Law No. (23) of 1984, in line with the requirements of international trade and in accordance with the standards, standards and agreements issued by It is accepted by international organizations and bodies concerned with foreign trade and transit transport, because of its importance in financial resources, supplementing the general budget, and achieving many social, economic and political goals for the countries of origin (exporting), transit countries (transit countries) and destination countries (the last destination) for goods to serve All Parties